Опыт применение метода управления по целям МВО на современном предприятии - Тешабаев, А. Э. (My University, 2014)
В статье описан опыт применения метода Управления по целям – Management by Objective (MBO) на крупном современном предприятии и проблемы внедрения, его преимущества и условия необходимые для эффективного применения.

Article describes the experience of implementation and usage of MBO - Management by Objective on large modern industrial company, problems of implementa- tion, achievements and conditions for successful usage of method.
Implementation and using MBO – Management by Objective in large modern company
Keywords: управление по целям; Management by Objective (MBO); цели; goals and objectives; мотивация персонала; motivation of employees; решение проблем; problem-solving